Customer Satisfaction Affected by Service Quality with the Scale of Service Quality in Hotels (SSQH) Method - Utama, Adi (Almana : Jurnal Manajemen dan Bisnis, 2024)
Service quality is a characteristic of a product or service that has advantages in satisfying real or implied needs. Customer satisfaction is a feeling of pleasure or disappointment that arises after comparing performance with expectations. This study aims to determine how customer quality affects consumer satisfaction. This is To measure service quality in the hotel sector, namely the Scale of Service Quality in Hotels (SSQH). The research method used is quantitative while the type of research is causal. The research sample consisted of 96 people who were visitors to hotels in the city of Bandung. The data analysis technique used is a multiple linear regression test, which tests the coefficient of determination, and the hypothesis using the SPSS 26 program. The results of the study show that partially accommodation, employee attitudes, and behavior, interaction with customers, employee skills, food and beverage quality, front desk quality, room quality, safety and security, friendliness, and waiting time have an influence on customer satisfaction. The test results simultaneously show that service quality has an effect on customer satisfaction.